Modelo estocástico para la predicción de la velocidad del viento - Hernández, E.; García, R. (Revista Tiempo y Clima, 2014)
On the basis of dady average wind speed data, a forecasting stochastic model has been built. Since one of the main influences in wind speed is the synoptic pattern over the measurement point, a new rnodel has bee elaborates taking into account the rneteorological information. The model obteined with the meteoroIogical input gives a better perfomance that the univariate one.